Upper Ocean Response Mechanisms to Pre-Monsoon and Post-Monsoon Cyclones in the Bay of Bengal - Siraj Uddin Md Babar Chowdhury; Anik Karmakar; Md Enamul Hoque; Md Minarul Hoque; Tabassum Hossain Tahsin; Showmitra Chowdhury (Ocean-Land-Atmosphere Research)
Tropical cyclones are intense and frequent natural hazards in the Bay of Bengal (BoB), leading to substantial losses of life and property along coastal areas. Understanding the seasonal variations and environmental factors that influence cyclone behavior in this region is essential for effective disaster preparedness and mitigation. This study conducts a comparative analysis of pre-monsoon and post-monsoon tropical cyclones of identical categories on upper oceanic parameters, including sea surface temperature (SST), sea surface salinity (SSS), sea level pressure (SLP), mixed layer depth (MLD), chlorophyll-a, and Ekman transport in the BoB. SSTs exhibit seasonal variation during cyclonic events, with pre-monsoon temperatures ranging from 29 to 31 °C, compared to post-monsoon of 28 to 29 °C. Freshwater inflow from rivers substantially influences salinity, resulting in lower salinity during the pre-monsoon period. Precipitation analysis reveals stronger convective activity during post-monsoon cyclones, typically producing more intense rainfall. SLP and wind speed data indicate that post-monsoon cyclones generate stronger winds and lower pressure than those occurring in the pre-monsoon season. Cyclones induce intense vertical mixing with MLD dynamics, indicating shallow mixing depths (3 to 11 m) in the northern Bay and moderately deeper depths (30 to 42 m) in the south. Elevated post-monsoon chlorophyll-a levels (9.9 to 14.4 mg/m³) suggest increased oceanic upwelling. Ekman transport patterns reflect wind-driven surface water horizontal movement influenced by cyclone track and intensity. Additionally, the lagged empirical time (LET) correlation analysis reveals key delayed ocean–atmosphere interactions, offering novel insight into temporal dependencies among upper ocean parameters during cyclone evolution. The findings demonstrate notable seasonal differences in upper ocean conditions between pre-monsoon and post-monsoon cyclones, revealing the important role of seasonality in shaping cyclone intensity and oceanic responses.